More indications for redox-sensitive cysteine residues of the Arabidopsis 5-aminolevulinate dehydratase - Wittmann, Daniel; Wang, Chao; Grimm, Bernhard (Frontiers in Plant Science, 2024)
Redox-dependent thiol-disulfide switches of cysteine residues are one of the significant posttranslational modifications of proteins to control rapidly their stability, activity, and protein interaction. Redox control also modulates the tetrapyrrole biosynthesis (TBS). Among the redoxdependent TBS enzymes, 5-aminolevulinic acid dehydratase (ALAD) was previously recognized to interact with reductants, such a thioredoxins or NADPH-dependent thioredoxin reductase C. In this report, we aim to verify the redox sensitivity of ALAD and identify the redox-reactive cysteine residues among the six cysteines of the mature protein form Arabidopsis. Based on structural modelling and comparative studies of wild-type ALAD and ALAD mutants with single and double CysSer substitutions under oxidizing and reducing conditions, we aim to predict the dimerization and oligomerisation of ALAD as well as the crucial Cys residues for disulfide bridge formation and enzyme activity. The Cys404Ser mutation led to a drastic inactivation of ALAD and redox-dependent properties of ALAD were severely impaired, when Cys71 was simultaneously mutated with Cys152 or Cys251. Cys71 is located in a flexible N-terminal arm of ALAD, which could allow intramolecular disulfide bridges with Cys residues at the surface of the remaining globule ALAD structure. As a result, we propose different roles of Cys residues for redox control, catalytic activity and Mg 2+dependent assembly.